Wiris Quizzes: a continuous assessment system with automatic feedback for online mathematics - Remei Calm; Ramon Masià; Carme Olivé; Núria Parés; Francesc Pozo; Jordi Ripoll; Teresa Sancho-Vinuesa (Ediciones Universidad de Salamanca, 2013)
<!--[if gte mso 9]> 0 0 1 148 815 USAL 6 1 962 14.0 <![endif]--> <!--[if gte mso 9]> Normal 0 21 false false false ES JA X-NONE <![endif]--><!--[if gte mso 9]> <w:LsdException Locked="false" P